Perancangan dan Implementasi Program Aplikasi Presensi Berbasis Website dengan Metode Waterfall - Arif Nur; Ari Abdillah (LKP KARYA PRIMA KURSUS, 2025)
Nurul Hakim Jakarta Elementary School still uses a manual attendance system for teachers, which is vulnerable to data manipulation, delays in recording, and inefficiencies in attendance recap. Additionally, the absence of a digital system for submitting leave or sick requests often results in late communication to school administrators. Therefore, a modern solution is needed to replace the conventional method with a more efficient and accurate system. This study aims to design and develop a web-based attendance application equipped with GPS location validation, photo upload as attendance proof, and online submission for leave and sick requests. The application was developed using the Waterfall method, which includes requirement analysis, system design, implementation, and testing. The application was built with PHP programming language using the Laravel framework and supported by a MySQL database. The results show that the system can record attendance in real time, reduce the potential for data manipulation, and simplify the monitoring and reporting process for administrators. The system also allows teachers to perform attendance without visiting the administrative office. In conclusion, the application enhances operational efficiency, data transparency, and the overall quality of attendance management at MI. Nurul Hakim Jakarta.